1976
DOI: 10.1037/0096-1523.2.3.401
|View full text |Cite
|
Sign up to set email alerts
|

Early versus late stages of processing and their relation to functional hemispheric asymmetries in face recognition.

Abstract: To determine whether perceptual asymmetries for faces occur at early or late stages of stimulus analysis, subjects compared the members of a pair of faces which appeared in the right or left visual field, either to each other or to a previously presented sample. The first two experiments established that manual reaction times were consistently shorter to left-field presentation only when test faces were compared for identity to a memorized sample (Experiment 2), but not when they were compared to each other (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
3
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 41 publications
7
80
3
1
Order By: Relevance
“…If the right-field advantage for "same" responses is proposed to result from a left-hemisphere superiority in extracting symmetry, for example, then it is difficult to explain why, when "same" responses alone were analyzed, visual field by symmetry interactions were not obtained (since the implication would be that the effect should disappear when pairs were asymmetric). On the other hand, if there are things inherent in "same" and "different" responses per se which are lateralized to the left and right hemispheres, respectively, then it becomes difficult to explain the frequent failure of the same-different factor to interact with visual field (Atkinson & Egeth, 1973;Egeth, 1971;Moscovitch, Scullion, & Christie, 1976). Clearly, more research is needed to discover the exact reasons for obtaining such interactions (Bagnara et al, 1982;Cohen, 1973;Egeth & Epstein, 1972).…”
Section: Experiments 2 Methodsmentioning
confidence: 99%
“…If the right-field advantage for "same" responses is proposed to result from a left-hemisphere superiority in extracting symmetry, for example, then it is difficult to explain why, when "same" responses alone were analyzed, visual field by symmetry interactions were not obtained (since the implication would be that the effect should disappear when pairs were asymmetric). On the other hand, if there are things inherent in "same" and "different" responses per se which are lateralized to the left and right hemispheres, respectively, then it becomes difficult to explain the frequent failure of the same-different factor to interact with visual field (Atkinson & Egeth, 1973;Egeth, 1971;Moscovitch, Scullion, & Christie, 1976). Clearly, more research is needed to discover the exact reasons for obtaining such interactions (Bagnara et al, 1982;Cohen, 1973;Egeth & Epstein, 1972).…”
Section: Experiments 2 Methodsmentioning
confidence: 99%
“…It might be deemed that these judgements consist of very early stage of the letter stimulus processing. With nonverbal stimulus materials (face), Moscovitch, Scullion, and Christie (1976) examined the functional hemisphere asymmetries at different stages of processing. In their first experiment, subjects judged if the paired faces were identical or not.…”
Section: Discussionmentioning
confidence: 99%
“…Moscovitch, Scullion, and Christie (1976) examined whether cognitive asymmetries for faces occurred at early or late stages of stimulus analyses. They showed that a consistent left visual field superiority was absent in early precategorical processing stages, while in a later higher order processes strong left visual field superiority was demonstrated.…”
mentioning
confidence: 99%
“…In fact, it has been suggested that recognition memory responses and frequency estimation are not made from the same sources of information (Wells, 1974), although what these sources are and how they differ from each other is not altogether clear (Hintzman, 1976). 17 Multiple processing systems and multiple channel conceptions are today more the rule than the exception in the study of sensory processes (Graham & Nachmias, 1971;Trevarthen, 1968). sented in the left visual field (De Renzi Si Spinnler, 1966;Moscovitch, Scullion, & Christie, 1976), and (b) that the recognition of emotional expressions shows the same right-brain superiority (Suberi & McKeever, 1977).…”
Section: Feeling and Thought: Two Systems?mentioning
confidence: 99%